Social Spirals through Everyday Group Life: Settings and Group Styles in a Comparative Perspective - Citroni, Sebastiano (Frontiers in Sociology, 2018)
Everyday group life is generally neglected in the study of the ongoing shifts affecting voluntary associations. This paper is grounded on a comparative ethnography of three Milanese associations affected by transformations in forms of voluntary participation, repertoires of action and in their relations with public institutions. The study focuses on group styles and settings to ascertain the role played by everyday group life in shaping the implications of these transformations for the production of inclusive outcomes by the observed associations. The author introduces three different results produced by the studied associations and account for them with the same overall argument, that focus on practices and spaces shaping everyday group life. The main findings illustrate that everyday group life works both as a filter through which transformations produce consequences and also as a site of autonomous elaboration through which associations’ outcomes are made and unmade.